2018
DOI: 10.3847/1538-4357/aae520
|View full text |Cite
|
Sign up to set email alerts
|

Maximally Dusty Star-forming Galaxies: Supernova Dust Production and Recycling in Local Group and High-redshift Galaxies

Abstract: Motivated by recent observations suggesting that core-collapse supernovae may on average produce ∼0.3 M of dust, we explore a simple dust production scenario which applies to star-forming galaxies in the local environment (the Magellanic Clouds and possibly the Milky Way) as well as to high redshift (sub-millimeter, QSO, Lyman break) galaxies. We assume that the net dust destruction (due to supernova reverse shock, shocks in the interstellar medium, or astration) is negligible on a timescale of 1 Gyr, in which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 160 publications
(268 reference statements)
6
32
0
Order By: Relevance
“…Some dust destruction, but not a significant amount, by SNe would be allowed in these cases as the derived dust yields are above 0.1M . This is in line with the result of Gall & Hjorth (2018) that dust in distant galaxies (including A2744_YD4) was formed by SNe, which requires very little dust destruction. Again, the required dust yields per AGB star for these three galaxies are significantly above the theoretical limit, so AGB stars have not contributed substantially to the dust production in these galaxies.…”
Section: Resultssupporting
confidence: 91%
“…Some dust destruction, but not a significant amount, by SNe would be allowed in these cases as the derived dust yields are above 0.1M . This is in line with the result of Gall & Hjorth (2018) that dust in distant galaxies (including A2744_YD4) was formed by SNe, which requires very little dust destruction. Again, the required dust yields per AGB star for these three galaxies are significantly above the theoretical limit, so AGB stars have not contributed substantially to the dust production in these galaxies.…”
Section: Resultssupporting
confidence: 91%
“…The average dust produced per SN is ∼0.1 M e for all three metallicities. We note that dust formation in SN ejecta is still uncertain and measurements range from∼10 −6 to 1 M e of dust per SN (Temim et al 2015;Gall & Hjorth 2018;Sarangi et al 2018), but SNe would have to form dust beyond the highest mass range of the observed values in order to compensate for the dust destruction rate.…”
Section: Binary Population and Spectra Synthesis Modelsmentioning
confidence: 88%
“…A recent study by De found that observed galaxy scaling relations are better fit by longer grain lifetimes and less efficient grain growth, supporting this interpretation. Gall & Hjorth (2018) have also suggested that the relationship between dust and stellar masses can be explained by inefficient dust destruction processes, although they offer rapid replenishment of dust in the ISM as an alternative interpretation. This overestimation of the destruction efficiency would only be the case if the objects we investigate are representative of SNRs in general, which is not necessarily true given that we were able to select only three from a sample size of hundreds.…”
Section: Discussionmentioning
confidence: 99%